KAJIAN RELASI ARSITEKTUR CANDI ERA MAJAPAHIT DENGAN VASTUSASTRA-MANASARA - Ruth Meiliani Surya; Harastoeti Dibyo Hartono (Riset Arsitektur (RISA), 2021)
Abstract- Vastusastra is a text which discusses Indian architecture which is published in several books, included Manasara. Vastusastra contains guidline for building Indian construction, including religious building such as temples. Although the narrative was made for the construction of temples in India, it turns out that there are some elements in vastu that also found in Mataram Kuno temples. This raises questions about the relationship of Indian architecture with Majapahit, which was the era after Ancient Mataram, given the Hindu-Buddhist influence still existed in the Majapahit era. To find out this, vastusastra-Manasara was used as a benchmark to find out the elements of the Majapahit temple which was influenced by India, especially South India which was thought to have a more dominant influence than North India on temple architecture in Indonesia. This study uses a descriptive method with a qualitative approach by describing the figure and mass-space layout of Majapahit temples that have been selected as the object of research and compared with vastusastra-Manasara's narrative using reference objects to facilitate analysis in order to find out the relations of the Majapahit era temples with vastusastra-Manasara narrative. Based on the results of the study, it was found that the temples of the Majapahit era still have relations with vastusastra-Manasara narrative when viewed in terms of figure and mass-space layout. But the relationship between the two can be said to be increasingly decreased. The re-domination of the original culture of Indonesian society in the Majapahit era and the influence of other cultures such as China is thought to be the cause of the waning influence of India on the architecture of the Majapahit temple. This led to the fusion of culture in the Majapahit temple and resulted in variations of new temples that had never existed before. Key Words: candi, majapahit, temple, vastusatra, manasara, relation